Metafora Tangan dalam Idiom Bahasa Jepang Berdasarkan Teori Metafora Konseptual - Dita Rachmawati (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2019)
This thesis is a conceptual metaphor research which analyse the element te â€˜handâ€™ in the Japanese idioms. The purpose of this research is to know the te 'hands' image scheme in Japanese idioms and analyze it based on the conceptual metaphors. The data source in this research were taken from the dictionary of idiom â€œiitai naiyou kara gyakuhiki dekiru reikai kanyouku jitenâ€ by Inoue Muneo. The amount of the data found and analysed were 59 and the amount of data presented were 15. The results of data analysis describe the idiom with the main element of the hand are filled with metaphorical expressions because the hand is the most used body part for activities. The results of the analysis also show eight concepts of hand, which are : HAND as ACTIVITIES/JOB, POSSESSION, LINK, ATTITUDE, TACTICS, CAPABILITY/SKILLS, SUPPORT, and EXPERTISE.To understand the concept of hand, it is useful to not only use ontological metaphors analysis, but in terms of the hand that has a spatial orientation, it must be analyse with orientational metaphors.